2009
DOI: 10.1002/fut.20364
|View full text |Cite
|
Sign up to set email alerts
|

Expiration‐day effects—An Asian twist

Abstract: This study examines the intraday trading activities of index stocks on the common expiration day of index derivatives. In Hong Kong, index futures and index options use an Asian-style settlement procedure. All contracts are settled against the estimated average settlement price, an arithmetic average of the underlying cash index taken every five minutes on the expiration day. Trading volume and total trade count on the expiration day are both found to be higher than normal. Most important, trading intensifies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The Hong Kong market also uses Asian-style settlement procedure, where the contracts are settled against the estimated average settlement price, which was the arithmetic average of the underlying cash index taken every 5 minutes on the expiration day. Fung and Yung (2009) found that though the trading was higher on the expiration day and was concentrated around 5-minute marks, there was no evidence of price reversal on the following day. They concluded that the use of "Asian-style settlement procedure reduces the market pressure at contract expiration dates by spreading index-related trades over a period of time."…”
Section: Expiration Day Effectmentioning
confidence: 92%
“…The Hong Kong market also uses Asian-style settlement procedure, where the contracts are settled against the estimated average settlement price, which was the arithmetic average of the underlying cash index taken every 5 minutes on the expiration day. Fung and Yung (2009) found that though the trading was higher on the expiration day and was concentrated around 5-minute marks, there was no evidence of price reversal on the following day. They concluded that the use of "Asian-style settlement procedure reduces the market pressure at contract expiration dates by spreading index-related trades over a period of time."…”
Section: Expiration Day Effectmentioning
confidence: 92%
“…The comparison between the conclusions obtained by Chow et al (2003) and Fung and Jung (2009) revealed that the results of the analysis of expiration-day effects can vary depending on both the period under study and the method of the research. Alkebäck and Hagelin (2004) suggested that the daily data may be unable to properly reflect the effects and, thus, the conclusions based on high-frequency data should be perceived as more reliable.…”
Section: Volume Effectsmentioning
confidence: 94%
“…Volume effects have been investigated on several markets and also mostly confirmed on the spot markets of Germany (Schlag 1996), Sweden (Alkebäck and Hagelin 2004), India (Vipul 2005;Debasish 2010;Tripathy 2010;Narang and Vij 2013;Mahalwala 2016), Poland (Morawska 2007), China (Fung and Jung 2009), Spain (Illueca and Lafuente 2006), and Taiwan (Chow et al 2013).…”
Section: Volume Effectsmentioning
confidence: 95%
See 2 more Smart Citations